Conversion of poly-isoprene based rubber to value-added chemicals and liquid fuel via ethanolysis: Effect of operating parameters on product quality and quantity. (15th January 2020) - Ahmad, Nabeel; Ahmad, Nauman; Maafa, Ibrahim M.; Ahmed, Usama; Akhter, Parveen; Shehzad, Nasir; Amjad, Um-e-salma; Hussain, Murid; Javaid, Momina
Abstract: Liquefaction of poly-isoprene based rubber (PIR) was performed using ethanol as a solvent for the production of liquid fuel and chemicals. An autoclave batch reactor was used to perform the ethanolysis of PIR at different temperature ranges (250–375 °C), with different ethanol to PIR ratio (0.5:1 to 4:1), and at different reaction times (15–75mins). The experimental results showed that a maximum yield of 86 wt % was achieved at temperature of 325 °C, ethanol to PIR ratio 1/1, and reaction time of 30 min. This liquid oil yield is about 14% higher than the yield obtained from the pyrolysis of PIR at 500 °C and about 10% higher than the yield obtained from hydrothermal liquefaction of PIR at 375 °C. Moreover, the utilization of ethanol in the process was also incorporated and product yields were redefined. Furthermore, ethanol contributed to enhance the quality of liquid-oil, particularly in term of viscosity, acidity, and energy density. Furthermore, the FTIR analysis showed methyl and methylene were most dominating functional groups found in the liquid product and GCMS analysis identified that they were presented by alkenes, aromatics, and alkyls. Graphical abstract: Image 1 Highlights: PIR was converted to bio-oil via ethanolysis. Maximum liquid of 85.98 wt% was obtained at optimum conditions. This yield was considered 13.98% higher as compared to yield obtained by pyrolysis. d -limonene (32.86%) and isoprene (27.76%) were identified as major compounds.